IDENTIFIKASI TINGKAT KEASAMAN TANAH GAMBUT MENGGUNAKAN LOGIKA FUZZY INFERENCE SISTEM (FIS) - Devia kartika (Teknik Informatika, 2018)
In the agricultural sector, land is a factor that plays a very important role in determining agricultural business. Soil fertility is one of the determinants of the success of agricultural business. Each region has varying degrees of soil fertility and depends on the type of soil and its geographical location. One way to choose the right land to plant is to see the level of acidity. Not all plants are suitable to be planted especially in peat soils that have different acidity levels. This study presents the design of soil acidity detection system for plant species using fuzzy logic method and using Matlab is used to determine the type of plant according to data from agriculture experts, which is expected to assist farmers in choosing the right type of plants in accordance with certain soil acidity level. The measurement results obtained are in accordance with the calculation and land criteria that have been done in certain areas. Decision-making soil acidity level requires input and output variables. The input variables consist of soil and fertilizer weathering in addition to the output variables which consist of soil acidity using MATLAB. The variable yields 17 rules that are used to determine the acidity of the soil. A case gets a very small difference value between using manual calculation and MATLAB.